Using Action Research in Business: Developing New Practical Framework of Financial Planning Process for a New Franchise System - Mohd Harif, Mohd Amy Azhar; Perry, Chad (Journal of Business Management and Accounting, 2016)
Franchising is the fastest growing method of doing business these days, however, there is little academic research to guide or regulate industry practices. Thus, this research investigated the financial planning process in developing a new franchise system. This  study  used  action  research  methodology  to  develop  a  new  practical  framework of financial planning for a new franchise system within the Malaysian government department  franchise  regulators.  Three  main  action  research  cycles  were  conducted with  three  new  franchise  systems  seeking  to  register  with  the  Registrar  of  Franchise Malaysia (ROF). To triangulate the findings of the action research, the researcher also presented  them  at  a  National  Franchise  Workshop  (NFW).  These  activities  showed that the process of financial planning for a new franchise system should comprise 14elements with specific linkages. These practical frameworks for financial planning in a new franchise system were adopted by the ROF to be used as guideline in the process of  developing  a  new  franchise  system  and  serve  as  evaluation  tools  for  franchise registration.
Keywords: Franchising; action research; qualitative research